Polymorphisms in interleukin genes and their association with the risk of recurrent pregnancy loss - Cui, Yajie; Tian, Li; Wang, Ting; Lu, Na (Genes & Genetic Systems, 2019)
Interleukins play important roles in pregnancy. Altered expression and splicing of various interleukins have been linked to the pathophysiology of recurrent pregnancy loss. Polymorphisms in interleukin genes can affect the expression and/or splicing of their respective genes and thus influence the risk of recurrent pregnancy loss. In this work, we examined the association between the IL1B rs16944, IL1B rs1143634, IL6 rs1800795, IL6 rs1800796, IL10 rs1800896 and IL18 rs187238 polymorphisms and recurrent pregnancy loss risk in a Chinese population. Study subjects comprised 598 idiopathic recurrent pregnancy loss patients and 603 controls. The genotyping was accomplished by PCR-RFLP. Regression analysis was performed to evaluate the disease association. After adjustment by Bonferroni correction, only the IL1B rs16944 and IL6 rs1800796 polymorphisms were significantly associated with risk of recurrent pregnancy loss. The heterozygous TC genotype of IL1B rs16944 had an adjusted odds ratio (aOR) of 1.4209 (1.1302–1.8929) (P = 0.0019), while the homozygous CC genotype had an aOR of 1.7398 (1.2133–2.3203) (P = 0.0008). A significant association was also observed for the C allele [aOR = 1.3747 (1.1296–1.8972)] (P = 0.0003). For IL6 rs1800796, the heterozygous CG genotype, the homozygous GG genotype and the G allele had aORs of 0.7342 (0.4412–0.8423) (P = 0.0016), 0.5424 (0.1768–0.7865) (P = 0.0014) and 0.7009 (0.4511–0.8034) (P = 0.0007), respectively. In summary, the IL1B rs16944 and IL6 rs1800796 variants were associated with an increased and a decreased recurrent pregnancy loss risk, respectively.